The Rgg1518 transcriptional regulator is a necessary facet of sugar metabolism and virulence in Streptococcus pneumoniae. Issue 3 (10th August 2021) - Shlla, Bushra; Gazioglu, Ozcan; Shafeeq, Sulman; Manzoor, Irfan; Kuipers, Oscar P.; Ulijasz, Andrew; Hiller, N. Luisa; Andrew, Peter W.; Yesilkaya, Hasan
Abstract: Rggs are a group of transcriptional regulators with diverse roles in metabolism and virulence. Here, we present work on the Rgg1518/SHP1518 quorum sensing system of Streptococcus pneumoniae . The activity of Rgg1518 is induced by its cognate peptide, SHP1518. In vitro analysis showed that the Rgg1518 system is active in conditions rich in galactose and mannose, key nutrients during nasopharyngeal colonization. Rgg1518 expression is highly induced in the presence of these sugars and its isogenic mutant is attenuated in growth on galactose and mannose. When compared with other Rgg systems, Rgg1518 has the largest regulon on galactose. On galactose it controls up‐ or downregulation of a functionally diverse set of genes involved in galactose metabolism, capsule biosynthesis, iron metabolism, protein translation, as well as other metabolic functions, acting mainly as a repressor of gene expression. Rgg1518 is a repressor of capsule biosynthesis, and binds directly to the capsule regulatory region. Comparison with other Rggs revealed inter‐regulatory interactions among Rggs. Finally, the rgg1518 mutant is attenuated in colonization and virulence in a mouse model of colonization and pneumonia. We conclude that Rgg1518 is a virulence determinant that contributes to a regulatory network composed of multiple Rgg systems. Abstract : The important human pathogen Streptococcus pneumoniae can sense the sugars present in the respiratory mucus including galactose and mannose by using a transcriptional regulator called Rgg1518. This regulator controls the expression of a large number of genes involved in vital metabolic processes and capsule, the most important pneumococcal virulence determinant. The absence of Rgg1518 adversely affects the microbe's virulence and its survival in the host.